2015
DOI: 10.1523/jneurosci.2278-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional Modulation of Recognition Memory

Abstract: Perirhinal cortex (PER) has a well established role in the familiarity-based recognition of individual items and objects. For example, animals and humans with perirhinal damage are unable to distinguish familiar from novel objects in recognition memory tasks. In the normal brain, perirhinal neurons respond to novelty and familiarity by increasing or decreasing firing rates. Recent work also implicates oscillatory activity in the low-beta and low-gamma frequency bands in sensory detection, perception, and recog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 74 publications
0
19
1
Order By: Relevance
“…Studies have used visually stimuli in the upper visual field which require approach behaviors (Harvey, Collman, Dombeck, & Tank, 2009; Scott, Constantinople, Erlich, Tank, & Brody, 2015). Conversely, other studies have employed stimuli which occur in the lower visual field, and which require avoidance behaviors (Ho et al, 2015; Manita et al, 2015). However, in these studies the stimuli have usually been presented a large number of times and have been associated with either a positive or negative outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have used visually stimuli in the upper visual field which require approach behaviors (Harvey, Collman, Dombeck, & Tank, 2009; Scott, Constantinople, Erlich, Tank, & Brody, 2015). Conversely, other studies have employed stimuli which occur in the lower visual field, and which require avoidance behaviors (Ho et al, 2015; Manita et al, 2015). However, in these studies the stimuli have usually been presented a large number of times and have been associated with either a positive or negative outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The PER has been shown repeatedly to be necessary for the recognition of familiar objects (Ennaceur and Aggleton, ; Winters and Bussey, ) and to have different neural signatures for familiar and novel objects (Zhu and Brown, ; Wan et al, ). Recently, our laboratory showed that PER stimulation at specific frequencies influences behavioral exploration of familiarity and novelty (Ho et al, ), suggesting the PER is part of a circuit that upregulates and downregulates exploratory behavior based on current surroundings and internal states.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the lateral entorhinal cortex could help place objects in the context of other local/proximal cues (Neunuebel et al, ). Thus, while perirhinal cortex is sufficient to signal object familiarity (Ho et al, ), interactions with the hippocampus, via entorhinal cortex, are required for object‐based associative learning. The present study examined this information transfer using a combination of lesions and c‐ fos imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Models of medial temporal lobe function distinguish two pathways that converge upon the hippocampus, one for “what (item)” information, the other for “where (context)” information (Eichenbaum et al, ; Ranganath and Ritchey, ). The perirhinal cortex occupies a central position in the “what” pathway as it conveys high‐resolution object information to the entorhinal cortex and hippocampus (Fernandez and Tendolkar, ; Bussey and Saksida, ; Deshmukh et al, ; Suzuki and Naya, ), while also signaling the novelty/familiarity of this same information (Brown and Aggleton, ; Ho et al, ). Evidence for this “what” pathway includes findings from rat lesion studies, which show how perirhinal cortex damage disrupts object recognition (Brown and Aggleton, ; Winters et al, ), alongside evidence for the joint involvement of the perirhinal cortex with the hippocampus for associative object recognition tasks, such as discriminating a familiar object set in a novel spatial location (Barker and Warburton, ; Warburton and Brown, ).…”
Section: Introductionmentioning
confidence: 99%